Cultured meat from muscle stem cells - Khiflie, Nur Noha Syarafana; Abd Rashid, Nur Amira; Razali, Nor Faizah; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
Livestock is important for the growth of humans even a thousand years back. Nowadays, the population of people has increased over the years. This scenario may give problems to all people around the world such as the lack of raw material, land, water and also enhance the greenhouse gas (GHG) emissions which will jeopardize the Earth. The idea of cultured meat has been developed in certain countries such as Israel, Netherlands and Australia since 2015 in order to overcome the problems these days and for new generations. Cultured meat or in vitro meat comes with 3 steps: 1. Selection of starter cells 2. Treatment of growth medium and 3. Scaffolding that is well-explained in this report. Cultured meat is the production where we can generate the meat that is edible and full with nutrients as conventional meat has. Besides, the product also generates more benefits for the areas of cost, energy and time consumed, production, health, environment and animals. Aside from many benefits of cultured meat, there are few implications that can affect the environment, economical issues and society regarding the regulation approval of cultured meat. The comparison of nutritional value and protein content in cultured meat and conventional meat can be seen as the conventional meat being naturally beneficial in these areas, however further research could overcome this issue. Therefore, the chance of getting cultured meat into the market is quite risky yet very profitable.